1982
DOI: 10.1161/01.res.50.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemic response of the coronary circulation to brief diastolic occlusion in the conscious dog.

Abstract: This study was undertaken to determine whether coronary blood flow can be regulated in response to coronary arterial occlusions briefer than a single diastole. The possible involvement of metabolic vs. myogenic mechanisms in such regulation was investigated. Eleven conscious dogs with experimentally produced complete heart block, chronically implanted electromagnetic flow probes, and pneumatic occluders on the left circumflex coronary artery were studied. Diastolic coronary occlusions lasting 100 to 400 msec w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Tension-time index was calculated from the left ventricular pressure tracing, and stroke volume was obtained from numerical integration of the phasic aortic flow waveform. The coronary perfusion pressure has been shown to correspond closely to the aortic pressure for the purpose of these calculations (21). The five beats immediately preceding each intervention were analyzed and averaged to provide the control hemodynamic parameters for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Tension-time index was calculated from the left ventricular pressure tracing, and stroke volume was obtained from numerical integration of the phasic aortic flow waveform. The coronary perfusion pressure has been shown to correspond closely to the aortic pressure for the purpose of these calculations (21). The five beats immediately preceding each intervention were analyzed and averaged to provide the control hemodynamic parameters for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The following hemodynamic parameters were calculated for each cardiac cycle: mean aortic systolic and diastolic pressure, mean systolic and diastolic coronary blood flow and diastolic coronary vascular resistance index (mean aortic diastolic pressure divided by mean diastolic coronary flow). The coronary perfusion pressure has been shown to correspond closely to the aortic pressure for the purpose of these calculations (18). Data from at least 5 beats prior to each intervention were analyzed to provide baseline hemodynamie parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory have shown that a 400-msec diastolic coronary artery occlusion results in a reactive hyperemic response lasting for several beats (18). Similarly, the increased cardiac demand following a single ventricular electrical extra-activation leads to a brief increase in coronary blood flow which cannot be explained by the transient increase in coronary perfusion pressure that accompanies the potentiation of ventricular contractility (19).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…All substances were administered by injection by the same person throughout the study, and the injection rate was 2 ml/sec. In group A, the following injections were given: 6 ml arterial blood (drawn from the coronary artery catheter), 6 ml coronary venous blood (obtained via the coronary sinus catheter), 3 and 6 ml isotonic saline, 3 and 6 ml hypertonic glucose (30% solution, which corresponds to 1400 mOsm/kg), and 6 ml sodium metrizoate (Isopaque Coronar 370, Nyegaard & Co A/S), which is an ionic contrast medium with calcium added and with an osmolality of 2100 mOsm/kg.…”
mentioning
confidence: 99%